They are free, but we are after them. Journalism and entertainment in “Custe o que Custar” - Gutmann, Juliana Freire (2009)
In this article, we analyze the articulation between journalism and entertainment in the television program Custe o que Custar, a creation of the Eyeworks-Cuatro Cabezas, that was launched in Brazil in March of 2008 by the Bandeirantes Net. From the application of the Methodology of the Group of Research in TV News´ Analysis, we identify that the CQC´s mode of address appeals, at the same time, to journalism and to entertainment and invites the viewers to share the articulation between the two instances, without damage or deformation of none of them. We believe that CQC unites journalism and mood without losing sight of premises and values that constitute journalism as a social institution - despite the fact that these premises and values are reconfigured. We find, in the CQC, the construction of the journalistic credibility; the resource to the notions of evenness, objectivity, actuality, public interest and social responsibility; the affirmation of the independence of the political field and a very interesting way to deal with the economic field.